The effect of STEM supported research-inquiry-based learning approach on the scientific creativity of 7th grade students - Merve Gül Kırıcı; Hasan Bakırcı (Journal of Pedagogical Research, 2021)
This research aims to examine the effect of science, technology, engineering and mathematics (STEM) supported research-inquiry-based learning approach on the scientific creativity of 7th grade students.  A pre-test and post-test quasi-experimental design with the control group was adopted into the research. The participants of this research were 64 secondary school students, 35 of whom were in the experimental group and 29 of whom were in the control group. To examine the effect of the intervention, a scientific creativity test was used and Wilcoxon signed ranks test, Mann-Whitney U-test, dependent t-tests were performed to analyse the data. The results revealed a significant difference in scientific creativity test scores, favoring the experimental group. When the subscales originality, flexibility and fluency were analysed, a significant difference in favor of the post-test of the experimental group was noted. However, no significant difference was found between the pre-post test scores of the control group. This means that the intervention has the potential to increase the scientific creativity of seventh grade students. Drawing on the results of this research, we argue that STEM supported education should be used to identify the appropriate steps of the engineering design process for secondary school and high school levels.